Sensitivity Analysis of the Coupled Dynamic Behavior of Vehicles in Collision with Semirigid Guardrails - Chun Liu; Hong-Jun Liao; Jun Chen; Qian-Qian Deng (Shock and Vibration)
To quantitatively study the coupled dynamic behavior of vehicles in collision with semirigid guardrails, a coupled numerical model is established based on the finite element method. This model comprehensively integrates the nonlinear dynamic behavior of both the vehicle body and the guardrail structure. We validate the numerical results by comparing them with experimental findings and theoretical empirical formulas, confirming the accuracy of the coupled numerical model. This quantitative study investigates the influence of vehicle speed, column wall thickness, and collision angle on this coupled dynamic behavior to help optimize practical guardrail engineering designs. The results indicate that the sensitivity values of the collision speed, column wall thickness, and collision angle according to the baseline model are 1.0, 1.0, and 0.741, respectively. The parameters with higher sensitivity values are the key factors to consider in designs. Thus, the coupled numerical model can be used to optimize the design of semirigid guardrails in practical engineering.